Imunomodulator Zinc (Zn) Terhadap Pertumbuhan Parasitemia Pada Mencit BALB/C Yang diinfeksi Plasmodium Berghei ANKA - Ni Nyoman Ariwidiani; Rosnalia Nyoman Widyan; Wulan Ratia Ratulangi (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Malaria infection is a disease with significant mortality, especially in tropical and subtropical areas. The rupture of infected red blood cells will stimulate the role of the immune system, CD4+ T cells will release IFN-γ cytokines that play a role in stimulating the activation of CD8+ T lymphocytes, which play a role in controlling parasitemia. Zinc is known to be involved in T cell signaling that can increase the expression of IFN-γ cytokines that play a role in parasite elimination. Methods: 20 minutes after being infected with P. berghei ANKA, were divided into 4 groups. Group 1-2 were given zinc as therapy with a concentration of 10mg/ml with a dose of 50mg/kgBW and 100mg/kgBW. Group 3 was a negative control (NC) given 0.5% sodium carboxylmethyl cellulose (CMCNa). Group 4 was a positive control treated with dihydroartemisinin-piperaquine (DHP) with a concentration of 187.2 mg/kgBW. Therapy was given for 4 days of observation, and parasitemia was observed every day after 24 hours of the first administration until the 4th day after administration. Results: Significant results were obtained in the parasitemia inhibition analysis after zinc administration on day 3 (p = 0.027) and day 4 (p = 0.001). Based on the results of the analysis, it was shown that zinc has anti-malarial activity that can inhibit the growth of parasitemia in test mice. Conclusion: Zinc as an antimalarial showed effectiveness in reducing parasitemia in BALB/c mice infected with P. berghei ANKA.